History of art - Janson, H. W. (Horst Woldemar), 1913-1982.; Janson, Anthony F. (New York : Abrams, 1991)
Relates the history of art from prehistoric cave paintings to the present. Includes 1182 illustrations
part 1. Ancient world -- chapter 1. Prehistoric and ethnographic art -- chapter 2. Egyptian art -- chapter 3. Ancient Near Eastern art -- chapter 4. Aegean art -- chapter 5. Greek art -- chapter 6. Etruscan art -- chapter 7. Roman art -- chapter 8. Early Christian and Byzantine art -- part 2. Middle Ages -- chapter 1. Islamic art -- chapter 2. Early Medieval art -- chapter 3. Romanesque art -- chapter 4. Gothic art -- part 3. Renaissance, Mannerism, and the Baroque -- chapter 1. "Late Gothic" painting, sculpture, and the graphic arts -- chapter 2. Early Renaissance in Italy -- chapter 3. High Renaissance in Italy -- chapter 4. Mannerism and other trends -- chapter 5. Renaissance in the north -- chapter 6. Baroque in Italy and Germany -- chapter 7. Baroque in Flanders, Holland, and Spain -- chapter 8. Baroque and Rococo in France and England -- part 4. Modern world -- chapter 1. Neoclassicism and Romanticism -- chapter 2. Realism and Impressionism -- chapter 3. Post-Impressionism -- chapter 4. Twentieth-century painting -- chapter 5. Twentieth-century sculpture -- chapter 6. Twentieth-century architecture -- chapter 7. Twentieth-century photography
Includes bibliographical references (pages 820-826) and index
Keywords: Art -- History